Analisis Kaidah Urf pada Fatwa DSN-MUI No. 54 tentang Syariah Card - Rizaludin Rizaludin; Hari Susanto; Jaih Mubarak (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
Humans as social beings cannot be separated from interaction with others, especially in fulfilling their daily needs, in economic activities, buying and selling transactions have a large enough portion to be discussed and studied, at the beginning of its development, buying and selling that occurs is still traditional, along with the times, found a medium of exchange called money, either in the form of metal or fiat money, the existence of money makes it easier for humans to make transactions. Innovation in the economic world, especially the banking world, is always dynamic, one of the emerging products is the sharia card or sharia credit card. The Indonesian Ulema Council through the National Sharia Council then provides direction through its fatwa No. 54 regarding sharia cards, in its fatwa sheet one of the arguments used is fiqh rules that discuss urf, so this study aims to discuss the relationship between the emergence of sharia card products and the urf argument that be included. Have the needs of the Islamic economic community in Indonesia reached the urf level and explain the mechanism of the sharia card contract listed on the DSN-MUI fatwa sheet No. 54. This research is a qualitative research based on library research with the main reference being turast books based on ushul fiqh and qawaid fiqhiah. After reviewing and paying attention to the concepts of urf in the two branches of science above, it was found that the needs of the community which were the main reason for the birth of this sharia card product had not yet reached the level of urf or habit, it only reached the level of مَا تَعُمُّ بِهِ الْبَلْوَى which is a condition where the use of credit cards in transactions has become common, but the results of this study do not necessarily result in this fatwa being automatically invalidated, because in its reference, DSN-MUI includes arguments and other rules that aim to strengthen sharia principles that apply to sharia cards. or Islamic credit card. This research is expected to be an example of studying fatwa sheets issued by DSN-MUI, so that it can become additional knowledge for those who want to study a fatwa. Keywords: Urf, Fatwa, Syariah Card